Strengthening public health graduate competencies through field-based learning: A case study at Diponegoro University - Nurjazuli, Nurjazuli; Widjaranko, Bagoes; Rokhman, Fathur (Jurnal Cakrawala Pendidikan, 2026)
Field-Based Learning Practice (FBLP) has become a key component in the curriculum of the Faculty of Public Health, Diponegoro University. This learning model emphasizes hands-on experience through community engagement, aiming to bridge the gap between theory and real-world health challenges. However, evidence remains limited on how public health competencies are systematically demonstrated and assessed within structured field-based learning outputs. FBLP places students directly in community settings, where they engage in a structured problem-solving cycle that includes problem identification, root cause analysis, and the design and implementation of intervention strategies. This study adopts a descriptive case study approach to analyze 20 student group reports from FBLP conducted between 2023 and 2024. Data were collected through documentation review, using the Problem-Solving Cycle stages and Knowledge–Attitude–Practice (KAP) indicators as analytical lenses to assess competency evidence. Findings show that FBLP significantly strengthens both technical and interpersonal competencies. Across reports, students most consistently demonstrated competency in problem prioritization (MCUA), determinant-based causal analysis (fishbone/Blum framework), and action planning, while monitoring and evaluation were less consistently documented. Students demonstrated improved problem-solving abilities, a deeper understanding of public health dynamics, and better readiness to work in multidisciplinary environments. The application of Multiple Criteria Utility Assessment (MCUA), Fishbone, and How-How analysis methods enriched learning and supported holistic intervention design. This study contributes methodological insight by demonstrating how report-based indicators can be used to evaluate competency development within a structured field-learning cycle, with implications for curriculum design and competency-based assessment. FBLP is proven to be an effective pedagogical strategy for preparing students to respond to the complex demands of public health practice. This model may serve as a reference for other institutions seeking to enhance competency-based education through experiential learning.